Better brand management through design thinking - Rodica Pamfilie; Adina-Gabriela Croitoru (Amfiteatru Economic Journal, 2018)
The world is evolving fast, and in a global society that is developing at an astounding pace, borders of any kind are eliminated one at 0 a time. Moreover, the competition between companies is becoming fiercer and fiercer, so the differentiation of products and services has gradually turned into a real necessity. In this context, design thinking is one of the elements that is currently drawing new directions, often being associated with the innovation process and the gain of competitive advantages. Recent studies show that design principles applied at a strategic level, especially in the field of innovation, significantly increase its success rate. Design thinking focuses on obtaining solutions and is action-oriented, providing all the necessary premises in order to discover new market needs and, moreover, to satisfy them. Another extremely important element in the current global context is brand, which gives the main points of differentiation for offers existing on the market. A correct and efficient management of the brand supports the creation of strong emotional relationships with consumers, bringing competitive advantages, especially by increasing their loyalty. As a result, brand management is an area of particular interest, and design thinking, together with innovation, can successfully support its specific actions, bringing with them the benefits of creativity, that translate into defining new concepts for attracting consumers and their trust. This article addresses aspects of design and design thinking, as elements that support a successful brand management, taking the tourism domain, which is currently the world's fastest growing industry, as a case study. The authors sought to study the connection between design, design thinking and brand management by correlating two studies, one of them conducted among consumers and the other one, among economic agents. Thus, questionnaires were addressed to consumers in order to identify their perception on design and design thinking, but also to economic agents in order to determine their actions in this regard. The way design and design thinking influences customers' consumption behavior represents a starting point for building brand management strategies, indicating either the need to enhance their use or, on the contrary, the lack of need for design.
Keywords: L83; M31; O31; Z32; 330; brand management; design thinking; innovation; development strategy; added value